2009
DOI: 10.1002/jbt.20259
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane and its analogues inhibit CYP1A1 and CYP1A2 activity induced by benzo[a]pyrene

Abstract: CYP1A1 and CYP1A2 enzymes metabolize polycyclic aromatic hydrocarbons (PAHs) to the reactive oxyderivatives. PAHs can induce the activity of both enzymes, which increases its conversion and enhances risk of carcinogenesis. Thus, the inhibition of CYP enzymes is recognized as a cancer chemoprevention strategy. A well-known group of chemopreventive agents is isothiocyanates, which occur naturally in Brassica vegetables. In this paper, a naturally occurring sulforaphane and its two synthetic analogues isothiocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 33 publications
2
24
0
1
Order By: Relevance
“…Among the two isomers of sulforaphane, the naturally-occurring R-isomer was the more efficient (Abdull Razis et al, 2012d). Furthermore, phenethyl isothiocyanate, erucin and sulforaphane suppressed, in concentration-dependent manner, the benzo[a]pyrenemediated rise in rat hepatic CYP1A1 mRNA levels in rat slices (Abdull Razis et al, 2011c;2012d), in concordance with studies reporting that these isothiocyanates antagonise the benzo[a]pyrene-mediated increase in the O-deethylation of ethoxyresorufin in both rat and human precision-cut liver slices (Hanlon, 2009a;Konsue, 2010a), as well as in human mammary tumour cell line Mcf7, where sulforaphane inhibited benzo[a]pyrene-mediated CYP1A2 induction (Skupinska et al, 2009). It is possible that the effect of isothiocyanates on the O-deethylation of ethoxyresorufin is due, to some extent, mechanism-based inhibition associated with these compounds (Yoxall et al, 2005;Hanlon et al, 2008a).…”
Section: Interaction Of Isothiocyanates and Glucosinolates With The Asupporting
confidence: 71%
“…Among the two isomers of sulforaphane, the naturally-occurring R-isomer was the more efficient (Abdull Razis et al, 2012d). Furthermore, phenethyl isothiocyanate, erucin and sulforaphane suppressed, in concentration-dependent manner, the benzo[a]pyrenemediated rise in rat hepatic CYP1A1 mRNA levels in rat slices (Abdull Razis et al, 2011c;2012d), in concordance with studies reporting that these isothiocyanates antagonise the benzo[a]pyrene-mediated increase in the O-deethylation of ethoxyresorufin in both rat and human precision-cut liver slices (Hanlon, 2009a;Konsue, 2010a), as well as in human mammary tumour cell line Mcf7, where sulforaphane inhibited benzo[a]pyrene-mediated CYP1A2 induction (Skupinska et al, 2009). It is possible that the effect of isothiocyanates on the O-deethylation of ethoxyresorufin is due, to some extent, mechanism-based inhibition associated with these compounds (Yoxall et al, 2005;Hanlon et al, 2008a).…”
Section: Interaction Of Isothiocyanates and Glucosinolates With The Asupporting
confidence: 71%
“…Administration of garlic in the diet showed an inhibition of CYP1A expression in aflatoxicosis in fish (T7) when compared to the control (group T2) (Figure 3). Natural organosulfur compounds, such as garlic, are considered potent chemopreventive compounds as they inhibit CYP1A1 and CYP1A2 directly (Skupinska, Misiewicz-Krzeminska, Stypulkowski, Lubelska, & Kasprzycka-Guttman, 2009;Guengerich & Shimada, 1991). Garlic appears therefore, to decrease the AFB1 toxicity there by alleviating the hepatic lesions and protecting the liver from damage induced by AFB1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activating the Nrf2-Keap1 signaling pathway, sulforaphane exerts actions such as modulation of some major cytochrome P450 enzymes involved in xenobiotic metabolism. It has been reported that sulforaphane inhibited cytochrome P450 (CYP)1A1 and CYP1A2 enzymes induced by polycyclic aromatic hydrocarbons in HepG2 and MCF7 mammary cancer cells 23 ; inhibited CYP1B1 in MCF-10A cells 24 , inhibited CYP2B1/2 in rat hepatocytes 17 ; inhibited CYP3A4 in human hepatocytes 25 ; however, sulforaphane up-regulated CYP1A2 in MCF-10A cells 24 . The underlying mechanisms of the actions of sulforaphane on cytochrome P450 expression is unclear, but may relate in part to cross-talk between the Nrf2 and Aryl hydrocarbon receptor (Ahr) pathways 26 .…”
Section: Molecular Targets Of Sulforaphane: Not Just Nrf2mentioning
confidence: 99%